House Dust Mite Allergies Among Elementary Students in a Semi-Rural Area - Maria Kaisar; Anastasia Hangestu; Airen Wang; Joyceline Chika Tanely; Putri Regita Anggraini; Soegianto Ali (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2026)
Allergies represent a chronic health concern among schoolchildren in Indonesia. The disorder is increasing in number but often underdiagnosed, particularly in semi-rural areas facing limited access to health services. This community service sought to facilitate access to initial allergy screening and increase awareness of the allergic status of elementary schoolchildren in the semi-rural area of Muaragembong, Bekasi. Allergy screening was conducted using the Skin Prick Test (SPT) method to detect sensitization to house dust mite (HDM) allergens Dermatophagoides pteronyssinus (Derp) and D. farinae (Derf) in 98 participants aged 6–13 years. Subsequent data analysis and interpretation aimed to enhance health awareness. The results indicated that the total prevalence of HDM sensitization reached 24.5%, with 7.1% of them sensitized to both allergens. This finding highlights the critical nature of the allergy issue and the need for its proactive intervention. Direct discourse about this discovery with parents/guardians and local healthcare services is pivotal to raise their awareness. Future efforts should prioritize the development of HDM avoidance protocols that require active parental participation in routine household cleaning as a community-based solution. Additionally, establishing formal referral networks to local health facilities, governments, and other policymakers is essential for ensuring ongoing allergy management.